The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3138/ptc.2011-42
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Concept of Leadership from the Perspective of Physical Therapists in Canada

Abstract: Purpose: To explore the concept of leadership from the perspective of physical therapists in Canada. Methods: A quantitative, cross-sectional nationwide study was performed using a Web-based survey distributed to all members of the Canadian Physiotherapy Association (CPA) with a registered e-mail address (n ¼ 6,156). Frequency distributions and percentages were obtained for all leadership characteristics, and chi-square tests were performed, with significance set at p < 0.05. Results: A total of 1,875 members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 11 publications
2
49
1
Order By: Relevance
“…Our earlier study 6 was the first to address physical therapists' perceptions of the characteristics required for leadership in health care. It provided a foundation for discussing leadership in physical therapy and the importance of leadership with respect to the profession's position in Canadian health care systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our earlier study 6 was the first to address physical therapists' perceptions of the characteristics required for leadership in health care. It provided a foundation for discussing leadership in physical therapy and the importance of leadership with respect to the profession's position in Canadian health care systems.…”
mentioning
confidence: 99%
“…It provided a foundation for discussing leadership in physical therapy and the importance of leadership with respect to the profession's position in Canadian health care systems. 6 One essential component of effective leadership is advocacy, which, according to the National Association of Healthcare Advocacy Consultants (NAHAC), ''enables clients and client communities to actualize choices and access resources.'' 7 The Essential Competency Profile for Physiotherapists in Canada defines an advocate as one who ''responsibly uses his or her knowledge and expertise to promote the health and wellbeing of individual clients, communities, populations, and the profession.''…”
mentioning
confidence: 99%
“…In a survey on leadership among Canadian physical therapists, the top-rated characteristics of physical therapy leaders were communication, professionalism, and credibility. 7 Formal leadership training in graduate programmes can develop these skills and could actually be an area of focus for PPCD degrees. Creating physical therapy leaders and advocates at early career stages is essential to establish our role within the health care system and sustain our profession in the competitive health care environment.…”
Section: Clinical Commentary On Mistry Et Almentioning
confidence: 99%
“…They found that 80% of respondents self-identify as leaders. 1 Their findings are an essential step toward the selfawareness that will allow physiotherapists to pursue leadership roles within the health care system.…”
mentioning
confidence: 99%
“…2 Desveaux and colleagues' study is well timed, as it recognizes the importance of leadership within the profession and identifies potential areas of impact for leadership development. 1 Furthermore, the Leadership Division is developing a curriculum of core competencies in professional self-awareness, modelling leadership behaviours, and acknowledging leadership qualities in others within the profession and across the health care system, 3 incorporating the key findings of Desveaux and colleagues' study. The curriculum also incorporates the seven roles identified in the Essential Competencies Profile for Physiotherapists.…”
mentioning
confidence: 99%